1972
DOI: 10.1111/j.1399-6576.1972.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Dihydroergotamine During Spinal Anaesthesia in Man

Abstract: Cardiac output was determined and arterial and pulmonary artery pressures were recorded during a control period, after spinal anaesthesia (Th I—III) and after administration of 1 mg dihydroergotomine (DHE) i. v. in 10 healthy males.After spinal anaesthesia, arterial and pulmonary artery pressures decreased, whereas heart rate and cardiac output remained unchanged. After administration of DHE, arterial pressure increased to control level, while pulmonary artery pressure increased significantly above that level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Subsequently, its dihydrated derivative, DHE, has been investigated as a vasocon strictor agent in spinal [ 1 ] and epidural anaes thesia [4] as well as in high epidural anaesthe sia and mild acute hypovolaemia [15], Based on the observation that ergotamine caused stimulation of isolated canine veins in con centrations about 350 times lower than nor adrenaline but the maximal responses to er gotamine were only one third those to nor adrenaline. Miiller-Schweinitzer and Stunner [10] suggested the concept of a partial ago nistic action of ergot alkaloids on the vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, its dihydrated derivative, DHE, has been investigated as a vasocon strictor agent in spinal [ 1 ] and epidural anaes thesia [4] as well as in high epidural anaesthe sia and mild acute hypovolaemia [15], Based on the observation that ergotamine caused stimulation of isolated canine veins in con centrations about 350 times lower than nor adrenaline but the maximal responses to er gotamine were only one third those to nor adrenaline. Miiller-Schweinitzer and Stunner [10] suggested the concept of a partial ago nistic action of ergot alkaloids on the vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroergot amine (DHE) has been found to be useful as a vasoconstrictor in a variety of circulatory dis orders including spinal anaesthesia [1], epi dural anaesthesia [4. 15] and orthostatic hy potension [9. II], Furthermore, the drug is used for the treatment of migraine [6] and, because of the acceleration of venous blood flow, in combination with heparin for the prevention of postoperative venous throm bosis and pulmonary embolism [12], How ever, while it is generally agreed that DHE does not enhance myocardial contractility [5], the relative importance of a mobilization of blood by constriction of venous capaci tance vessels versus an increase in the tone of arteriolar resistance vessels to raise the blood pressure during epidural anaesthesia remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study in healthy young men (mean age 24, range 19-49), high spinal anaesthesia was found to cause a fall in arterial blood pressure because of reduced peripheral vascular resistance, while filling pressures were slightly reduced and stroke volume remained unchanged (Bergenwald et al, 1972). Yet dihydroergotamine (DHE), which is considered to have more pronounced effects on capacity than resistance vessels, restored the arterial pressure by increasing peripheral resistance in areas with sympathetic block.…”
Section: Introductionmentioning
confidence: 99%
“…These haemodynamic events may result in more or less profound hypotension (11). In order to restore the blood pressure, an effort can be made to improve the peripheral vasomotor tone, capacitance vessel function and cardiac performance by the use of vasoconstrictors such as dihydroergotamine (12,13,14), or sympathomimetic drugs such as ephedrine (15,16,17) or prenalterol (18,19). We have recently re-ported on the central and splanchnic circulatory effects of dihydroergotamine (14) and ephedrine (1 7) in the treatment of arterial hypotension caused by high epidural anaesthesia in the dog.…”
mentioning
confidence: 99%